2016
DOI: 10.1096/fj.15-281097
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 1‐carbon metabolites and academic achievement in 15‐yr‐old adolescents

Abstract: Academic achievement in adolescents is correlated with 1-carbon metabolism (1-CM), as folate intake is positively related and total plasma homocysteine (tHcy) negatively related to academic success. Because another 1-CM nutrient, choline is essential for fetal neurocognitive development, we hypothesized that choline and betaine could also be positively related to academic achievement in adolescents. In a sample of 15-yr-old children (n= 324), we measured plasma concentrations of homocysteine, choline, and beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…In a sample of 15-year-old children ( n = 324), the sum of school grades in 17 major subjects were used as an outcome measure for academic achievement. Researchers showed that plasma choline level was significantly and positively associated with academic achievement, independent of socioeconomic status (SES) factors, and folate intake [53]. In randomized, double-blind, controlled feeding studies, maternal choline supplementation did not improve measures of infant memory or language development [54], but did improve infant information processing speed [55], bolstering support for prenatal choline supplementation.…”
Section: Role Of Choline In Maternal and Infant Nutritionmentioning
confidence: 99%
“…In a sample of 15-year-old children ( n = 324), the sum of school grades in 17 major subjects were used as an outcome measure for academic achievement. Researchers showed that plasma choline level was significantly and positively associated with academic achievement, independent of socioeconomic status (SES) factors, and folate intake [53]. In randomized, double-blind, controlled feeding studies, maternal choline supplementation did not improve measures of infant memory or language development [54], but did improve infant information processing speed [55], bolstering support for prenatal choline supplementation.…”
Section: Role Of Choline In Maternal and Infant Nutritionmentioning
confidence: 99%
“…The A1298C variant results in substitution of glutamate (Glu) to alanine (Ala) at codon 429 in the S-adenosylmethionine regulatory domain of the MTHFR protein [18, 19]. The MTHFR C677T genetic variant can lead to elevated levels of plasma tHcy and, thus, increased ischemic stroke risk [20, 21], data of which have been further confirmed in other studies [12, 13, 22]. tHcy is thought to increase thrombotic risk through induction of endothelial injury in the venous and arterial vasculature [23].…”
Section: Introductionmentioning
confidence: 99%
“…Вариант A1298C приводит к замещению глутамата (Glu) на аланин (Ala) в кодоне 429 в S-аденозилметио ниновом регулятор-ном домене белка МТГФР [17,18]. Генетический вариант МТГФР C677T может приводить к повышенным уровням ГЦ плазмы и, таким образом, к увеличению риска развития ИИ [19,20], что подтверждено в других исследованиях [8,9,21].…”
unclassified